MANAGEMENT OF IRREGULAR ASTIGMATISM AFTER CORNEAL ULCER WITH RGP CONTACT LENS IN PATIENTS WITH HIGH MYOPIA - Noviantari, I Gusti Agung Ratna; Handayani, Ariesanti Tri (Oftalmologi : Jurnal Kesehatan Mata Indonesia, 2023)
Introduction: RGP contact lenses are indicated for correcting refractive errors in cases of high myopia and irregular astigmatism due to changes in the corneal curvature. Case Report: A 30-year-old female came with complaints of redness, pain, glare, blurred vision, and yellow discharge and tearing on the left eye for 2 days, history of using Soft Contact Lens (SCL) since 10 years old due to myopia. Visual Acuity of the right eye (VOD)  with glasses was 6/12 and VA of the left eye (VOS) was 1/300. The patient was diagnosed with left eye corneal ulcer and was given levofloxacin eye drops, hydroxypropyl methylcellulose eye drops, and vitamin C 1000 mg. The left eye's corneal ulcer healed after three days, but the scarring left the cornea's surface uneven.. Patients were advised to replace the contact lenses with RGP contact lenses. After the RGP fitting, the appropriate size was obtained in both eyes and the patient adapted well with VOD RGP 1.0  and VOS RGP 1.0 False. The patient felt helped by the RGP contact lens.  Discussion: RGP was given because it helped reduce the bacterial infection risk. RGP has a higher oxygen transmissibility and maintains the cornea's curvature to become more regular. It can be utilized as an optical device to repair excessive myopia in addition to irregular astigmatism. Conclusion: RGP contact lens can be an option for irregular astigmatism after corneal ulcers due to the SCL use in patients with high myopia to provide good outcomes.